EqualBITE Gender equality in higher education - Robertson, Judy; Williams, Alison; Jones, Derek; Isbel, Lara; Loads, Daphne (Brill, 2017)
EqualBITE digs into the messy reality of higher education gender issues, presenting people's stories, experiences and frustrations and - more importantly - what can be done. University of Edinburgh students and staff share real-life experiences of gender challenges and opportunities, and their constructive responses. The book condenses current academic research into practical actions that do make a difference. EqualBITE is a pragmatic and positive response to gender issues in academia - a catalyst for creating a culture which is better for everyone.